A study on motivational factors among Generation Y in Petronas Gas Berhad / Norhidayu Mohd Sani - Mohd Sani, Norhidayu (Faculty of Business and Management, 2014)
Motivation is the most important factors influential organizational efficiency. Employee motivation is a valuable asset which delivers huge value to the organization in maintaining and strengthening its business and revenue growth. One of the crucial functions of management is to create enthusiasm among the employees to execute in the best of their abilities. This research was conducted to determine factors that influence to employee motivation among Generation Y in PETRONAS Gas Berhad. The motivational factors consist of salary and wages, training and development, flexibility hour alternatives and work environment were investigated in a sample of 50 employees who belongs to Generation Y by using questionnaires. The subjects are being selected by conducting simple random sampling method for getting relevant data.